INNOVATIVE TEACHING METHODS IN TEACHING (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
In the modern educational process, innovative teaching methods play a key role in improving the quality of education and motivating students. These methods include: Students work on real projects, which helps develop practical skills and critical thinking. Using multimedia resources, online platforms and applications to create an engaging learning environment. Introducing game elements into the learning process to increase student engagement and interest. Combining traditional teaching methods with online formats, which allows you to adapt the process to the individual needs of students. Students work in groups, which helps develop social skills and the ability to work in a team. Innovative teaching methods not only contribute to better assimilation of the material, but also form the skills in students necessary for successful professional activity in a rapidly changing world.